A Dictionary of Theatre Anthropology : the Secret Art of the Performer. - Barba, Eugenio (Taylor & Francis, 2005)
This the second English language edition of the classic text, ""A Dictionary of Theatre Anthropology"" subtly juxtaposes the visual demonstrations of the performers craft, from a wealth of Oriental and Occidental sources. Whereas most Western research is concerned with naturalism and psychological realism in acting, the ""Dictionary"" focuses on the performer's arduous and eclectic craft.